PENGEMBANGAN MODEL DIKLAT GURU SOSIOLOGI SMA TENTANG PEMBELAJARAN INKUIRI BERBASIS BUDAYA LOKAL - Gunarso, Gunarso; Sulasmono, Bambang Suteng (Kelola: Jurnal Manajemen Pendidikan, 2015)
This development study is aimed to develop a model of training for sociology teacherÂ using inquiry based on local culture. It is done through some steps which are recognizingÂ the potential and problems, formulating a design, composing and performing deviceÂ validation. Based on the research has resulted a module of training for inquiry learningÂ based on local culture validated and revised by experts. The module is ready to use forÂ training to improve teachersâ competence. The plannings done before training areÂ determining training needs through analyzing the needs of the organization deciding aÂ training program,composing an initial assessment and end of the craft success criteriaÂ for training.The implementation of training development about inquiry based on localÂ culture for sociology teachers is emphasized in making lesson plan containingÂ characters value in Sociology. Monitoring and evaluation for quality assessment doneÂ by filling out the questionnaire by the trainees so that they are able to know the responseÂ to the committee and speakers. While the evaluation of trainees can be done throughÂ tests and assignment of making learning about inkuiri RPP based on local culture.